2018
DOI: 10.1074/jbc.ra118.003547
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase selectively inhibited by the type II inhibitor SBI-0206965

Abstract: Inhibition of the metabolic regulator AMP-activated protein kinase (AMPK) is increasingly being investigated for its therapeutic potential in diseases where AMPK hyperactivity results in poor prognoses, as in established cancers and neurodegeneration. However, AMPK-inhibitory tool compounds are largely limited to compound C, which has a poor selectivity profile. Here we identify the pyrimidine derivative SBI-0206965 as a direct AMPK inhibitor. SBI-0206965 inhibits AMPK with 40-fold greater potency and markedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
103
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 63 publications
14
103
1
1
Order By: Relevance
“…It is important to note here that the inhibitor affects downstream effector, but not AMPK phosphorylation per se. 29 Collectively, our data suggest that Nischarin disruption promotes breast tumor development and AMPK signaling is important for Nischarin-mediated suppression of breast tumor.…”
Section: Samples Gave Two Bands; One Represents 250 Kda Full-lengthmentioning
confidence: 70%
“…It is important to note here that the inhibitor affects downstream effector, but not AMPK phosphorylation per se. 29 Collectively, our data suggest that Nischarin disruption promotes breast tumor development and AMPK signaling is important for Nischarin-mediated suppression of breast tumor.…”
Section: Samples Gave Two Bands; One Represents 250 Kda Full-lengthmentioning
confidence: 70%
“…With the recent identification of more specific AMPK inhibitors, such as SBI-0206965 (REF. 199 ), it will be interesting to examine whether delivery of AMPK inhibitors into the central nervous system might suppress appetite and promote weight loss.…”
Section: ) (Table 1)mentioning
confidence: 99%
“…This transient increase in peak glucose levels was attenuated by pre-treatment with AMPK/Uncoordinated (Unc)-51-like kinase (ULK-1) inhibitor SBI-0206965 (3 mg kg -1 ; Fig. 2A), which inhibits AMPK in vitro at nanomolar concentrations (18). Previous studies have shown that suppression or activation of hypothalamic AMPK activity can attenuate or stimulate hepatic glucose production, respectively (19-21), indicating that hypothalamic AMPK activity regulates hepatic glucose production (HGP).…”
Section: Resultsmentioning
confidence: 99%